Beyond stage-gate processes: How to successfully exploit technology in large engineering firms. (25th January 2011) - Goddard, Edward; Entwistle, Peter; Godman, James; Strachan, Peter
In this paper, a methodology is proposed to assist engineering firms in their management of technology development programmes. The methodology proposes an approach that provides opportunity for a technology programme to adapt to changing conditions before, after and during gated assessment. The purpose is to create and review information on the factors that influence exploitation, in order to inform the dynamic reshaping of technology programmes. This paper argues that a more flexible approach may be used to inform the changes that are needed on technology development programmes to achieve exploitation as an adjunct to the stage-gate approach.